Responsive Approaches on Self-reflection of One’s Own Type of Teacher Student: Selected Findings from a Seminar on Experiments - Fögele, Janis; Luber, Laura; Mehren, Rainer (Journal of Geography Education, 2019)
In everyday classroom practice, knowledge acquired in university is seldom drawn upon, instead novice teachers refer to practical routines that are inscribed deeply after years of schooling. To counteract this, an intensive reflection on a meta-level about their orientations is necessary. In the present project, seminars on experiments focussing on the unity of theory and practice were conducted with students initially. Following, 25 group discussions were held within the framework of this study, which have been analysed using the documentary method. Four types of teacher training students were reconstructed: studies within the framework of (a) performance, (b) practical application, (c) experience, (d) insight.